COMMON FIXED POINT THEOREM FOR A PAIR OF WEAKLY COMPATIBLE SELF-MAPPINGS IN FUZZY METRIC SPACE USING (CLRG) PROPERTY - Nemaala, Apparao; V. Dharmaiah, V. Dharmaiah (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In this paper we prove a common fixed point theorem for a pair of weakly compatible self-mappings in fuzzy metric space by using (CLRg) property. The result is extended for two finite families of self-mappings in fuzzy metric space by using the concept of pairwise commuting. An example is provided which demonstrates the validity of main theorem.